Predictors of Outcome after Laparoscopic Nissen Fundoplication - Islam El-Atiar; Gamal Almaadawy; Mohamed Naroz; Hazem Megahed; Ayman Abdelmaksoud (International Journal of Medical Arts, 2023)
Background: Laparoscopic Nissen fundoplication with posterior hiatal repair is now thought to be the best way to treat severe Gastroesophageal Reflux Disease with surgery [GERD]. Long-term studies have shown that it gives most patients good control of their reflux symptoms and good clinical outcomes.Aim of the work: This study aims to identify the predictive factors of the surgical outcomes of laparoscopic Nissen fundoplication.Patients and Methods: A prospective study that was carried out at the department of surgery, Faculty of Medicine, Al-Azhar University [Damietta] on 30 patients with GERD and or hiatal hernia. Laparoscopic Nissen Fundoplication was described for all patients and the possible complications [including pain, wound complications, recurrence, dysphagia, bleeding and esophageal or gastric injury] were discussed.Results: The mean age of the studied cases was 37.5±11.29 years. As regards their gender, 53.3% were females and 46.7% were male. In terms of BMI, the mean body mass index was 27.0±3.39, with 26.7% of the cases being over- weight and 26.7% being obese. We found a significant association between the patient's satisfaction and the psychiatric disorders [P= 0.18], in which 50% of the patients who are unsatisfied or partially satisfied had positive psychiatric disorders. We also found a significant association between the patient's response to surgery and their satisfaction at all follow-up periods [P = 0.001]. We found that Positive psychiatric disorders are the only statistically significant predictor of poor response.  The patients with positive psychiatric disorders have a risk of developing poor outcomes 10.55 times more risk than cases with negative psychiatric disorders [odds ratio =10.55;95% CI: 1.61-69.12].Conclusion: Psychiatric disorders are the most important predictor for poor outcomes after laparoscopic fundoplication.